Within-Firm Pay Inequality - Mueller, Holger M.; Ouimet, Paige P.; Simintzi, Elena (Review of Financial Studies, 2017)
Financial regulators and investors have expressed concerns about high pay inequality within firms. Using a proprietary data set of public and private firms, this paper shows that firms with higher pay inequality—relative wage differentials between top- and bottom-level jobs—are larger and have higher valuations and stronger operating performance. Moreover, firms with higher pay inequality exhibit larger equity returns and greater earnings surprises, suggesting that pay inequality is not fully priced by the market. Our results support the notion that differences in pay inequality across firms are a reflection of differences in managerial talent. Received March 14, 2016; editorial decision January 21, 2017 by Editor Itay Goldstein.